Integrating the Transportation Material in BIPA Learning at FPNU China - Anandha; Osman, Sharifah (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2024)
The Teaching of Indonesian as a Foreign Language (Bahasa Indonesia Bagi Penutur Asing or BIPA) is a means of introducing the Indonesian language and culture to the international community. This research discusses the teaching of transportation materials to BIPA learners at Fujian Polytechnic Normal University (FPNU) in China. Using the Contextual Teaching and Learning (CTL) theory regarding second language acquisition (SLA) in the integration of transportation material in BIPA learning. The approach used in this research is descriptive qualitative. The research was conducted by observing BIPA learning in the class, followed by recording the implementation of BIPA transportation material learning among respondents in the Indonesian Language Department at FPNU China. The findings showed that the transportation material helped BIPA respondents learn Indonesian through contextual and communicative methods. The material provided includes vocabulary related to types of public transportation in Indonesia. The research results showed that the material on Indonesia's transportation system provides a more contextual learning experience for respondents at FPNU China.